Crisis of the times - crisis of philosophy? - Błaszczak-Wacławik, Mirosława (Folia Philosophica, 2004)
The awareness of a crisis is common. «Crisis» is a keyword, which refers to numerous fields of life. The problem of the crisis of culture belongs to the most important issues of contemporary thought. The article is an attempt at presenting the main areas of a philosophical discourse about the crisis. There are a couple of semantic options prepared for the needs of systematization; these options include the content of crucial philosophical questions associated with the crisis, as well as directions of a philosophical quest for sense, essence and sources of the crisis. The idea of a crisis belongs to the main problems, which serve self-reflection and selfidentification in philosophy. The philosophical discussion about the crisis also concerns the crisis of the identity of philosophy and is contemporarily associated with a creation of new philosophical projects.